Acute antioxidant supplementation improves endurance performance in trained athletes - Bentley, D. J.; Dank, S.; Coupland, R.; Midgley, A.; Spence, I. (Research in Sports Medicine, 2012)
This study examined the acute effects of a single dose of an antioxidant (AO; Lactaway®containing pycnogenol) on time to fatigue (TTF). Nine trained cyclists [mean ± SD age 35 ± 10 yrs; body mass 71.6 ± 10.2 kg; VO2peak 63 ± 11 ml/kg/min] performed on two separate occasions a continuous protocol of 5 min at 50% of peak power output (PPO), 8 min at 70% of PPO, and then cycled to fatigue at 95% PPO. Four hours prior to the exercise protocol, the subjects consumed the supplement or a placebo (counterbalanced, double blind protocol). Cyclists, on average, rode for 80 s more in the Lactaway trial than they did in the placebo trial. There was considerable evidence (chances >/=94.5%) for substantial positive treatment effects for TTF and the other performance-related variables (excluding [BLa] at 95% PPO). Other studies are necessary to confirm these results and identify the mechanisms underlying the observed effects.